Object-oriented Oracle - Rahayu, Johanna Wenny (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
"The book covers comprehensive and fundamental aspects of the implementation of object-oriented modeling in a DBMS that was originated as a pure Relational Database, Oracle"--Provided by publisher
Includes bibliographical references and index. - Title from ebook home page (viewed on July 13, 2010)
Keywords: Oracle (Computer file); Object-oriented methods (Computer science)